Barriers to patient-centered human immunodeficiency virus (HIV) care with African American patients who use drugs: Social construction of the typical and ideal care visit. Issue 2 (3rd April 2017) - Carlberg-Racich, Suzanne; Roden, Lindsey
ABSTRACT: Background : A successful patient-provider relationship ensures that patients are treated as individuals and receive appropriate care for their unique circumstances. For this to occur, the relationship needs open communication and trust. African American persons who inject drugs (PWIDs) and who smoke crack cocaine are at elevated risks of poor health outcomes and are often lost to care. In addition, providers often experience difficulty serving this population. Although some barriers are documented in the peer-reviewed literature, this study sought to provide in-depth context to the relationship and how it is constructed. Methods : Individual, semistructured interviews were conducted with human immunodeficiency virus (HIV) care providers and their patients, specifically PWIDs and persons who smoke crack cocaine, in publicly funded HIV clinics in low-resource urban communities. n = 31 patients and n = 7 providers were interviewed about their perceptions of the other and the relationship. Interview transcripts were coded and analyzed for common themes, which were used to generate a conceptual, constructionist model of the HIV care visit. Results : Common patient themes included the tendency to describe providers in familial terms, match between their current provider and ideal provider, concern about stigma related to their use, and expression of unmet needs. Provider themes revealed less match with their ideal patient—preferring patients who were both abstinent and adherent, and expressing frustration with patient refusal to change. Conclusions : Thematic results were used to create a visual and conceptual model for the HIV care visit. The model demonstrates both the positive and negative perceptions that inform the visit, and the barriers that impede a more fruitful patient-provider dynamic with a shared power structure. Provider training in communication and other identified topics may begin to lay the foundation for a shift in this structure.